Role of Illyricum in Tetrarchic Wars - Gračanin, Hrvoje (Array, 2005)
Since the Marcomannic wars of Marcus Aurelius Antoninus in the second half of the 2nd century A.D., Illyricum gained steadily on importance because of its strategic significance: the security of Italy depended on stability of the middle Danube frontier. Illyricum was also perceived as the empire's most valuable and reliable recruiting ground. The 3rd century with its almost continous crisis saw heavy internal and external fighting especially in Illyrian provinces. As a result, the Illyrian troops and their commanders were advanced into position of not only providing the decisive defence for the Empire, but also of deciding on the holder of the imperial power. Many important military commanders of that time were of Illyrian origin or stationed in Illyricum, and a number of them rose to the throne, or tried to do so. Diocletian, who himself was an Illyrian by birth, recognized the role of Illyricum in his attempts to restore the Empire. Virtually all of the Augusti and Caesars of Diocletianic era were Illyrians. Galerius, who received Illyricum and Greece by Diocletian in A.D. 293 as his portion of the Empire, maintained the control of the middle Danube frontier having two of his nominees put in charge of the west Illyrian provinces: both Severus and Licinius received diocese of Pannonia, in A.D. 305 and 308 respectively, while Galerius commanded the rest of Illyricum, as well as Thrace. Galerius' direct control over Illyricum was of considerable importance for his move against Maxentius in Italy, athough Galerius failed to suppress the usurper. In the autumn of 308, Diocletian, urged by Galerius, called a conference at Carnuntum in Upper Pannonia (Pannonia Prima) to resolve the problems caused by civil war. The place of conference was deliberate: it was in the relative vicinity of Diocletian's palace in Dalmatia, was under Galerius' control, and was situated in the central part of the Empire, close to the main traffic routes connecting East and West. Illyricum played even more important role in the events following Galerius' death in A.D. 311. Illyricum and its adjacent region of Thrace were regular battlegrounds in the struggle between the pretenders for control over the Empire. There were decisive battles fought there between Licinius and Maximinus Daia (Campus Ergenus at Tzirallum near Adrianople in A.D. 313), and Constantine I and Licinius (Cibalae near Sirmium and Mardia near Adrianople in A.D. 316 (314?), Adrianople in A.D. 324). Both Licinius and Constantine tried to secure their positions in Illyricum as to neutralize the oponent and win upper hand. In A.D. 316 (314?), Licinius was left only in control of diocese of Thrace, while Constantine acquired all of Illyricum. This proved crucial, for in A.D. 324, the year of final confrontation, Constantine was able to use his strategic advantage and in three-month campaign inflict ultimate defeat on Licinius. This was the last act of tetrarchic wars, in which Illyricum played a prominent role.